Evaluation of Diagnostic Variables Normalization Methods for Sustainable Energy Development Index – Application for European Union Member States - Magdalena LIGUS; Piotr PETERNEK (Communications of International Proceedings, 2021)
The composite sustainable energy index could prove useful to evaluate both the state of the art and the progress of national energy towards sustainable development. However, different methods of normalization, weighting, and aggregation of data can produce different results of index values and the ranking of objects. The objective of the paper is to evaluate different methods of diagnostic variables normalization in application to simple additive weighting (SAW) method, as the most widely used method to obtain aggregate indices. We test different procedures to obtain Sustainable Energy Development Aggregated Index (SEDAI) to rank the EU Member States. We apply nine normalization methods and some measures of ranking quality. We found that the quotient type normalization gave the worst results. Another seven normalization methods gave similar results. We recommend that normalization method should be selected that is compatible with both the selected diagnostic variables and the ranking method chosen.
Keywords: SAW method; normalization methods; sustainable energy; aggregated index.